Predictors of Left Ventricular Outflow Tract Obstruction After Transcatheter Mitral Valve Replacement in Severe Mitral Annular Calcification: An Analysis of the Transcatheter Mitral Valve Replacement in Mitral Annular Calcification Global Registry. (20th October 2021) - El Sabbagh, Abdallah; Al-Hijji, Mohammed; Wang, Dee Dee; Eleid, Mackram; Urena, Marina; Himbert, Dominique; Chakravarty, Tarun; Holzhey, David; Pershad, Ashish; Fang, H. Kenith; Nejjari, Mohammed; Zahr, Firas; et al.
Abstract : Background: Several studies have evaluated preprocedural imaging predictors of left ventricular outflow tract obstruction (LVOTO) after transcatheter mitral valve replacement. The patient cohorts in these studies were heterogeneous and included patients with transcatheter mitral valve replacement in failed bioprostheses, annuloplasty rings, and severe mitral annular calcification (MAC). The goal of this study was to evaluate predictors of LVOTO specific to patients undergoing valve-in-MAC. Methods: This study included patients with severe MAC who underwent valve-in-MAC and had optimal quality preprocedural multidetector row computed tomography scans eligible for retrospective analysis. Baseline demographic, echocardiographic, and procedural data on these patients were collected. multidetector row computed tomography parameters were analyzed for association with LVOTO, defined as increase in mean LVOT gradient by ≥10 mm Hg with accompanying hemodynamic instability. Results: Seventy-one patients with optimal preprocedural computed tomography scans were included in this study (mean age, 72.5±13.5 years), 9 of which developed LVOTO (all female). Baseline mean LVOT area, neo-LVOT area (145.3 versus 270.9 mm 2 ; P =0.006), indexed neo-LVOT area (90.1 versus 157.4; P =0.05), and virtual transcatheter heart valve to septum distance (3.1 versus 6.9 mm; P =0.002) were lower in the LVOTO group. Expected % LVOT area reduction was higher in the latter group (58.3 versus 42.7%; P =0.008). In the univariable analysis, the baseline mean LVOT area, neo-LVOT area, indexed neo-LVOT area, and valve to septum distance were all significantly associated with LVOTO. Conclusions: The systolic mean LVOT area, neo-LVOT area, indexed neo-LVOT, expected percentage LVOT area reduction, and the valve to septum distance were associated with LVOTO after valve-in-MAC.